Molecular Characterization Analysis of Prevalent Infectious Bronchitis Virus and Pathogenicity Assessment of Recombination Strain in China - Wu, Zhiqiang; Fang, Huanxin; Xu, Zhouyi; Lian, Jiamin; Xie, Zi; Wang, Zhanxin; Qin, Jianpin; Huang, Benli; Feng, Keyu; Zhang, Xinheng; Lin, Wencheng; Li, Hongxin; et al. (Frontiers in Veterinary Science, 2022)
Infectious bronchitis virus (IBV) has always been a major pathogen threatening the chicken industry, and it has become more prevalent, as recombination events frequently contribute to the emergence of new IBV variants. In this study, chick flocks with respiratory symptoms were consciously monitored in eight provinces, and the IBV positive rate eventually rose to 17.6%. A total of 160 IBV strains were isolated and comparative analysis of the S1 gene revealed that QX-type, TW-type, 4/91-type, HN08-type, TC07-2-type, and LDT3-type exhibited IBV positive rates of 58.15%, 25%, 8.12%, 1.86%, 5.62%, and 1.25%. In addition, recombination analyses revealed that the four newly IBV isolates exhibited different recombination patterns. The CK/CH/JS/YC10-3 isolate likely originated from recombination events between strain YX10 (QX-type) and strain TW2575-98 (TW-type), the pathogenicity of which was assessed, comparing it with strain GZ14 (TW-type). The S1 gene data from these isolates indicate that IBV will consistently evolve through genetic recombination, likely causing a viral pattern recognition molecule or changing the viral pathogenicity and leading to larger outbreaks in chick populations in China.